Engineering carbon nanotubes as therapeutic nanocarriers of Tulbaghia violacea, Annona muricata, Dicoma capensis and Dodonaea viscosa plant-based extracts, targeting breast and colorectal cancer - Gwanzura, Takunda (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.